2020
DOI: 10.35241/emeraldopenres.13550.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and employees’ mental health: stressors, moderators and agenda for organizational actions

Abstract: Background: This paper examines the impact of coronavirus COVID-19 outbreak on employees’ mental health, specifically psychological distress and depression. It aims at identifying the main stressors during and post COVID-19, examining the main moderating factors which may mitigate or aggravate the impact of COVID-19 on employees’ mental health and finally to suggest recommendations from a human resource management perspective to mitigate COVID-19’s impact on employees’ mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
345
0
25

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(440 citation statements)
references
References 71 publications
(148 reference statements)
10
345
0
25
Order By: Relevance
“…adopted to reduce the spread of COVID-19 have resulted in a reduced workforce across many economic sectors [7], as well as a general perception of job insecurity [8], namely the fearful of job loss or worry about job continuation [9]. Perceived job insecurity has been found to be a fundamental stressor during the COVID-19 outbreak [10], as it has a negative impact on the individual's financial capacity due to the high risk of financial loss [11]. In relation to dentists, a survey conducted by the Irish Dental Association with 369 dentists reported that one-fifth of participants closed their practices temporarily or permanently, and that around three-quarters of the sample expected a financial loss of over 70% amid the COVID-19 outbreak [12].…”
Section: Introductionmentioning
confidence: 99%
“…adopted to reduce the spread of COVID-19 have resulted in a reduced workforce across many economic sectors [7], as well as a general perception of job insecurity [8], namely the fearful of job loss or worry about job continuation [9]. Perceived job insecurity has been found to be a fundamental stressor during the COVID-19 outbreak [10], as it has a negative impact on the individual's financial capacity due to the high risk of financial loss [11]. In relation to dentists, a survey conducted by the Irish Dental Association with 369 dentists reported that one-fifth of participants closed their practices temporarily or permanently, and that around three-quarters of the sample expected a financial loss of over 70% amid the COVID-19 outbreak [12].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for business sectors, the impacts of the COVID-19 pandemic have brought about tremendous disruption to the activities and operations of businesses in almost every industry (McKibbin & Fernando, 2020). Not only does the crisis pose financial threats to organizations, it also affects the work and psychological wellbeing of their employees affected by the crisis (Hamouche, 2020). The negative impacts of the crisis also exist in the educational sector (DePietro, 2020;Sahu, 2020): According to UNESCO (2020), the ongoing COVID-19 pandemic is causing widespread disruption to education globally.…”
Section: Introductionmentioning
confidence: 99%
“…During the lockdown schools and universities, as well as many workplaces, were closed and, except for emergency situations, even leaving the house was forbidden. This lockdown, which required many people to stay at home, thus, limiting their freedom of movement, is a highly unique situation, whose psychological consequences in the short-and medium-term are not yet known (Hamouche, 2020).…”
mentioning
confidence: 99%